Synergistic chemo-immunotherapy for osteosarcoma via a pH-responsive multi-component nanoparticle system - Li, Dapeng; Li, Yuanfan; Cang, Jie; Yan, Xianwen; Wu, Feipeng; Sun, Xuan; Zhang, Wenchao (Frontiers in Pharmacology, 2025)
IntroductionOsteosarcoma (OS) is the most common primary malignant bone tumor in pediatric populations. Its treatment is complicated by chemotherapy-induced toxicity and limited induction of immunogenic cell death (ICD).MethodsTo address these challenges, we developed a pH-responsive, multi-component nanoparticle system designed to co-deliver doxorubicin (DOX), monophosphoryl lipid A (MPLA), and a PD-1/PD-L1-targeting peptide, integrated with the immune-modulating polymer PEG-PC7A. The system was optimized using both one-factor-at-a-time (OFAT) and Box-Behnken design (BBD).ResultsThe optimized nanoparticles had a hydrodynamic size of 110 nm, high encapsulation efficiency (97.15%), and pH-sensitive drug release (91% at pH 6.5). In vitro studies showed enhanced ICD markers, including calreticulin exposure and ATP/HMGB1 release, aswell as synergistic dendritic cell maturation via dual STING/TLR4 pathway activation. In an orthotopic LM8 osteosarcoma model, the nanoparticles significantly suppressed tumor growth, promoted cytotoxic T lymphocyte infiltration, reduced regulatory T cells, and established long-term immune memory.DiscussionThe combination of ICD induction, innate immune activation, and checkpoint blockade reprogrammed the tumor microenvironment, amplifying anti-tumor immune responses. These results demonstrate the potential of this multifunctional nanoparticle platform as an effective immunochemotherapeutic strategy for osteosarcoma, offering enhanced therapeutic efficacy and reduced systemic toxicity.